Pelatihan Kemasan Digital Dan Pendampingan Manajerial Pengembangan UMKM Berbasis Kewirausahaan Pada Komunitas Pedagang LINTAS ALAP-ALAP Kendal - Setya Pramono; M. Masrukhan (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
This community service activity aims to provide alternatives to increase family income in strong trader community Lintas ALAP-ALAP Kendal Regency, focusing on diversification of selling products, and product packaging for digital marketing. Hoping to get maximum results maximum results, this activity is also carried out from the management side through organizational order and management of member management and mentoring for 6 months. mentoring for 6 months. The implementation of community service was carried out on September 27 September 2024, with digital marketing material, product diversification and financial management of MSMEs. financial management of MSMEs. The implementation of community service was carried out in conjunction with the quarterly konitas meetings which are held in rotation at the homes of the members, attended by 32 people. This first session activity was followed up with the assistance of members practicing product diversification material and digital marketing packaging. digital marketing packaging with quite satisfactory results as evidenced by the the creation of processed products that contain added value and modern product packaging. product packaging that is more modern. Participants who take part in community service activities are expected to be able to apply the material provided to be applied in trading activities every day to increase sales. every day to be able to increase sales.